The complex star cluster system of NGC 1316 (Fornax A) - Sesto, Leandro Alberto (2016)
This paper presents Gemini-gri high-quality photometry for cluster candidates in the field of NGC 1316 (Fornax A) as part of a study that also includes GMOS spectroscopy. A preliminary discussion of the photometric data indicates the presence of four stellar cluster populations with distinctive features in terms of age, chemical abundance and spatial distribution. Two of them seem to be the usually old (metal poor and metal rich) populations typically found in elliptical galaxies. In turn, an intermediate-age (5 Gyr) globular cluster population is the dominant component of the sample (as reported by previous papers). We also find a younger cluster population with a tentative age of ≈ 1 Gyr.